Integral-type contraction on orthogonal S-metric spaces with common fixed-point results and applications to fractional integral equations - Samuel, Benitha Wises; Mani, Gunaseelan; Ramulu, Shoba Sree; Thabet, Sabri T. M.; Kedim, Imed (Fixed point theory and algorithms for sciences and engineering, 2025)
In this article, we present common fixed-point theorems for contractions of integral type within the framework of orthogonal S -metric spaces. Examples are provided to illustrate the findings. This work extends and generalizes numerous results from existing literature. Furthermore, the theoretical results are reinforced through an application to a fractional integral equation.